1998
DOI: 10.1097/00000542-199803000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled Epidural Analgesia with Bupivacaine and Fentanyl on Hospital Wards 

Abstract: Patient-controlled epidural analgesia provides effective and safe postoperative analgesia on hospital wards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
101
1
11

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(126 citation statements)
references
References 27 publications
12
101
1
11
Order By: Relevance
“…The limited segmental spread of the thoracic epidural analgesia also minimizes motor blockade thus facilitating early mobilization. 21 The classic catabolic response to operation (the surgical stress response), a key pathogenic factor in postoperative morbidity, is attenuated by blocking the afferent neural stimulus with epidural local anesthetic. 22 Extensive epidural anesthesia (T4-Ss) is easily achieved by the thoracic route without approaching toxic local anesthetic concentrations and, when instituted before surgery and followed by epidural analgesia with local anesthetic, results in the greatest observed reduction of the perioperative stress response.…”
mentioning
confidence: 99%
“…The limited segmental spread of the thoracic epidural analgesia also minimizes motor blockade thus facilitating early mobilization. 21 The classic catabolic response to operation (the surgical stress response), a key pathogenic factor in postoperative morbidity, is attenuated by blocking the afferent neural stimulus with epidural local anesthetic. 22 Extensive epidural anesthesia (T4-Ss) is easily achieved by the thoracic route without approaching toxic local anesthetic concentrations and, when instituted before surgery and followed by epidural analgesia with local anesthetic, results in the greatest observed reduction of the perioperative stress response.…”
mentioning
confidence: 99%
“…Numerous studies have supported the use of PCEA with such solutions. Liu et al [1] studied 1030 patients using PCEA for postoperative pain control and found their mixture of bupivacaine 0.05% and fentanyl 4 mg.ml ¹1 to be safe and effective. Wiebalck et al [2] demonstrated the benefits of adding sufentanil to bupivacaine for postoperative PCEA.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have studied the use of a lipid-soluble opioid and local anaesthetic mixture for postoperative patient-controlled epidural analgesia (PCEA) [1][2][3]. While the use of such solutions has become commonplace, there is still much controversy regarding the use of a background infusion in PCEA for postoperative pain control.…”
mentioning
confidence: 99%
“…3 Ac cor ding to se ve ral studi es, TE A using a lo cal ana est he tic com bi ned with an opi o id can be con si de red as a com monly used stan dard met hod in the ma na ge ment of acu te posttho ra co tomy pa in. [4][5][6] The ma jo rity of stu di es ha ve shown that the use of a lo cal ana est he tic-opi o id com bi na ti on is as so ci a ted with sig ni fi cantly bet ter dyna mic pa in re li ef af ter tho ra cic sur gery than the com po nents of the mix tu re in fu sed alo ne. 3 The aim of pos to pe ra ti ve pa in ma na ge ment is to pro vi de go od sub jec ti ve com fort, to con tri bu te early re co very and to have a go od out co me af ter sur gery.…”
Section: Effects Of Preoperatively or Postoperatively Initiated Thoramentioning
confidence: 99%